Synthesis and characterization of novel oxazines and demonstration that they specifically target cyclooxygenase 2. Issue 15 (1st August 2015) - Srinivas, V.; Mohan, Chakrabhavi Dhananjaya; Baburajeev, C.P.; Rangappa, Shobith; Jagadish, Swamy; Fuchs, Julian E.; Sukhorukov, Alexey Yu.; Chandra; Mason, Daniel J.; Sharath Kumar, Kothanahally Shivaramu; Madegowda, Mahendra; Bender, Andreas; et al.
Graphical abstract